Performance evaluation of a multi-wavelength and multicast packet switch - Chen, Wen. (2009)
Nowadays the amount of Internet traffic in current backbone networks has grown enormously due to wide deployment of broad-band Internet access and new multimedia applications such as sensing data sharing and real-time streaming. The processing speed of the electronic switching will become a bottleneck for the next generation optical networks. Therefore, optical packet switching (OPS) is a long-term strategy for network evolution that exploits fast switching techniques to provide greater bandwidth efficiency, flexibility, functionality, and offer finer granularity.